Tratamento clínico de cães com diagnóstico presuntivo de doença do disco intervertebral - Baumhardt, Raquel (2015)
Intervertebral disc disease (IVD) is a common pathology in clinical neurology of dogs, representing 45.8% of neurological cases treated at Veterinary Hospital of the Universidade Federal de Santa Maria. The most affected segments are the thoracolumbar (T3-L3) and cranial cervical (C1-C5) of the spinal cord. The clinical sign occurs due a combination of the compressive effect of the disc material and the injury of impact on spinal cord, probably due to an extrusion. A clinical sign varies according to the affected segment of the spinal cord and the severity of the injury. It could be presented only by spinal hyperesthesia, whereas more severe injuries can lead to tetra / paraplegia with no nociception (deep pain) caudal to the lesion. Clinical management for IVD is generally indicated for dogs with hyperesthesia with or without minimal neurological deficits and consists of absolute rest in cage between four to six weeks. Surgery is the treatment of choice for dogs with severe neurological deficits (not ambulatory tetraparesis, tetraplegia, paraplegia with or without nociception in less than 48 hours) in dogs with unsuccessful of clinical management, or dog that have recurrence of disease. In contrast to the numerous studies evaluating the efficacy of surgical treatment in dogs with thoracolumbar and cervical IVD, studies demonstrating the effectiveness of conservative treatment are rare. The aim of this study was to identify dogs with presumptive diagnosis of thoracolumbar and cervical IVD who underwent clinical management and evaluate the response to therapy; and to analyze the effect of age, gender, duration of clinical signs, neurological degree and therapy, as prognostic factors in clinical outcome of the patient. Five hundred six neurological records were used to identify affected dogs (n = 379 thoracolumbar; n = 127 cervical), and was selected those patients with presumptive diagnosis of IVD submitted to clinical management as a first option. The outcome was satisfactory in 73.3% of cases of thoracolumbar IVD, and 92.7% of cases of cervical IVD, demonstrating that clinical management (cage rest, anti-inflammatory and analgesic opioid administration) is effective, especially in milder disease. Conservative treatment has a substantial rate of recurrence and neurological signs may be more severe than the first clinical presentation. The gender, age and duration of clinical signs has no prognostic effect on clinical outcomes of patients IVD of thoracolumbar and cervical, in the sample of the study.